A Comparative Study Of Consumers As Users Of Ios And Android Smartphones In Jakarta - Nuraga Budiman, Andika; Wicaksono, Hendra; Suyana, Hilma (Annpublisher, 2025)
Background. This study investigates the usage patterns of iOS and Android operating systems among users in Jakarta. Aim. We aimed to analyze the roles of brand image and lifestyle as independent and mediating variables affecting users' repurchase intentions. Methods. Our SPSS analysis surveyed 205 respondents (146 Android and 59 iOS users). Result. That brand image does not significantly influence Android users' repurchase intentions, indicating that other factors may be more critical in their decision-making. Similarly, lifestyle had no significant effect on iOS users' repurchase intentions, suggesting that lifestyle choices may not drive brand loyalty in this demographic. Additionally, our mediation analysis showed that flagship products impact consumers differently based on their operating systems, highlighting the complexity of consumer behavior in the tech market. Conclusion. This study underscores the nuanced interactions between brand image, lifestyle, and user intentions across different platforms. Implication: These findings provide important insights into the Jakarta market. They also highlight the need for further research in diverse contexts to fully understand the dynamics of brand image and repurchase intention across different consumer segments and geographical areas.